STRATEGI PENGEMBANGAN DESA WISATA JANGGA DOLOK KECAMATAN LUMBAN JULU KABUPATEN TOBA - Pradnyana, I Putu Wahyu Sastra (Jurnal Ilmiah Akomodasi Agung, 2024)
The Jangga Dolok Village is one of 19 village swhich included in the 2020-2024 National Medium-Term Development Plan (RPJMN) tobe developed into a Rural Tourism. The natural potential and cultural richness of Jangga Dolok Village could be a special attraction for tourists. The purpose of this research was to determine the development strategy of Jangga Dolok Rural Tourism, Lumban Julu District, Toba Regency. Data collection technique was using question list of interviews as well as documentation. SWOT analysis was adata analysis technique that used in this research. The results of the analysis shown the physical tourism potential of Jangga Dolok Village, including: panoramic views of rice fields, historic buildings, village atmosphere, and residential residents. Mean while the non-physical potential is in the form of traditionalarts, the hospitality of the people, the value system and custom soft he community, institutions and social systems. So that suitable tourism potential is developed in the form of agricultural tourism and cultural tourism.